Novel insights in classic versus relative glomerular hyperfiltration and implications on pharmacotherapy. Issue 1 (21st January 2023) - Bielopolski, Dana; Streja, Elani; Steinmetz, Tali; Rozen-Zvi, Benaya; Kalantar-Zadeh, Kamyar
Abstract : Purpose of review: Glomerular filtration rate (GFR) assessment and its estimation (eGFR) is a long-lasting challenge in medicine and public health. Current eGFR formulae are indexed for standardized body surface area (BSA) of 1.73 m 2, ignoring persons and populations wherein the ratio of BSA or metabolic rate to nephron number might be different, due to increased BSA, increased metabolic rate or reduced nephron number. These equations are based on creatinine, cystatin C or a combination of the two, which adds another confounder to eGFR assessment. Unusually high GFR values, also known as renal hyperfiltration, have not been well defined under these equations. Recent findings: Special conditions such as solitary kidney in kidney donors, high dietary protein intake, obesity and diabetes are often associated with renal hyperfiltration and amenable to errors in GFR estimation. In all hyperfiltration types, there is an increased intraglomerular pressure that can be physiologic, but its persistence over time is detrimental to glomerulus leading to progressive glomerular damage and renal fibrosis. Hyperfiltration might be underdiagnosed due to BSA standardization embedded in the formula. Hence, timely intervention is delayed. Reducing intraglomerular pressure in diabetes can be achieved by SGLT2 inhibitors or low protein diet to reverse the glomerulopathy process. Summary: Accurate identification of glomerular hyperfiltration as a pre-CKD condition needs accurate estimation of GFR in the above normal range should establish a threshold for timely intervention.